(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Since the emergence of soundtracks, the music industry has been largely driven by innovation. The technological advances of the 20th century have significantly impacted society and the economy. Rapid development and use of the internet, in particular, strongly transform the music industry—especially in terms of how music is created and consumed. In this study, we tried to examine the changes in the music industry resulting from digital technology advancements. Furthermore, we aimed to examine how Croatians have incorporated digital innovations into their music-listening practices. The study explores: (i) respondents’ usage of media players and music platforms, (ii) age and gender differences in respondents’ reactions to industry developments, and (iii) preferences for digital versus analog music formats. Conducted on a random sample of 146 Croatian respondents, the research reveals a strong influence of digitalization on the music industry, with respondents showing high adaptability to these changes. Participants identified accessibility and the availability of music content as key benefits of digitalization, while piracy was noted as its primary drawback. Additionally, no significant age-based differences were found regarding preferences for digital or analog formats. While respondents acknowledged certain advantages of analog formats, digital music remains equally, if not more, widely used.